Dinamika Pertukaran Partikel Pada Interaksi Nukleon-Nukleon Dalam Potensial Lokal - R Yosi Aprian Sari; Supardi S; Agung BSU; Arief Hermanto (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
The interaction of two nucleons in the form of protons and neutrons as a bound system in the local potential, known as the deuteron, has been investigated. Two-nucleon interaction potential field through the core will produce a nuclear force where the force between nucleons is generated by the exchange of mesons. One of the members of the group of meson particles is pion. Pion can be chargedπ + ,π -or neutral,π 0. Interaction potential form of the simplest is the exchange of one pion potential (OPEP), V OPEP , which has a radially independent of Yukawa potential. In this study, the first step taken is to perform discretization of the OPEP potential expression coupled with the equation of the boundary conditions due to the influence of interaction distances. The next step is to implement a programming technique to obtain the value associated with the potential influence of OPEP in the deuteron, the magnitudes of the static deuteron, such as a pion distance exchange, and mass estimates pion involved in this interaction.